Rapid creation of skin substitutes from human skin cells and biomimetic nanofibers for acute full-thickness wound repair. Issue 8 (December 2015) - Mahjour, Seyed Babak; Fu, Xiaoling; Yang, Xiaochuan; Fong, Jason; Sefat, Farshid; Wang, Hongjun
Highlights: Biomimetic nanofiber meshes support the attachment and proliferation of skin cells. Nanofiber-enabled cell layering allows for spatial organization of skin cells. Nanofiber-enabled cell layering leads to the formation of bilayer skin substitutes. Nanofiber-enabled bilayer skin substitutes exhibit sufficient mechanical strengths. Engineered skin substitutes facilitate wound closure with reepithelialization. Abstract: Creation of functional skin substitutes within a clinically acceptable time window is essential for timely repair and management of large wounds such as extensive burns. The aim of this study was to investigate the possibility of fabricating skin substitutes via a bottom-up nanofiber-enabled cell assembly approach and using such substitutes for full-thickness wound repair in nude mice. Following a layer-by-layer (L- b -L) manner, human primary skin cells (fibroblasts and keratinocytes) were rapidly assembled together with electrospun polycaprolactone (PCL)/collagen (3:1, w/w; 8%, w/v) nanofibers into 3D constructs, in which fibroblasts and keratinocytes were located in the bottom and upper portion respectively. Following culture, the constructs developed into a skin-like structure with expression of basal keratinocyte markers and deposition of new matrix while exhibiting good mechanical strength (as high as 4.0 MPa by 14 days). Treatment of the full-thickness wounds created on the back of nude mice with various grafts (acellular nanofiber meshes, dermal substitutes, skin substitutes and autografts) revealed that 14-day-cultured skin substitutes facilitated a rapid wound closure with complete epithelialization comparable to autografts. Taken together, skin-like substitutes can be formed by L- b -L assembling human skin cells and biomimetic nanofibers and they are effective to heal acute full-thickness wounds in nude mice.